0019 Mapping injury data to inform targeted approaches to prevention. (26th April 2015) - Stewart, Camille; Pyle, Laura; Smith, Dwayne; Bensard, Denis; Moulton, Steve; Reiter, Sean
Abstract : Statement of purpose: Data available on unintentional injuries at state and county levels are insufficient for effectively planning prevention efforts at a neighbourhood level. Concentrating interventions in neighbourhoods at greatest risk helps improve the programmatic and financial efficiency of limited prevention resources, and enables practitioners to more effectively demonstrate outcomes measures. Methods/Approach: We queried paediatric t2rauma registry data (N=5, 380), over a 4 year period from two Level I Trauma Centres, and also statewide Emergency Department visit data for paediatric injuries (N = @111, 000) for all Colorado hospitals in 2013. Data was analysed by age, mechanism of injury, zip code of residence, payer source and more, to produce geographic maps that allow local I. P. practitioners and partner agencies a visual representation of where a disproportionate volume of injuries are occurring. Integrating U.S. Census data on population demographics (i.e., race/ethnicity, household income, etc.) provides additional contextual information that allows for refinement of program efforts. Results: We have identified Colorado zip codes of mechanism-specific high risk (i.e., injury "hot spots") that will be used to build neighbourhood capacity to address primary prevention efforts. Adjusting for confounding factors, zip codes with fewer educated individuals and higher populations had higher hospital charges. Conclusions: Injury burdens can vary greatly among communities in the same geopolitical area, and result in higher costs for treating paediatric trauma. Significance and contribution to the field: Children's Hospital Colorado has initiated steps to implement The Prevention Institute's recommendation to "… share healthcare data to map patterns of … injury and create community improvements, " found in their document A Checklist of Strategies for Health Care-Community Prevention Integration . This approach also aligns with the six levels on the Spectrum of Prevention. This type of analysis can be used to focus prevention efforts in the areas of greatest need, and can also inform resource allocation for publicly and privately funded prevention efforts, support for injury-related public policy initiatives, and more.